Dialekt jako exponent stylových hodnot komunikátu - Krčmová, Marie (Stylistyka, 2000)
The present article is based on an analysis of a series ofreviews which are stylized as texts written by a person lacking higher education and living outside the cultural centre ofthe country. On the background of neutral means of expression the author frequently uses dialectisms at all levels oflanguage. The texts as a whole could be labelled as postmodern. They are full of contrasts - quotations of and allusions to texts written in standard language are intertwined with dialect. This coexistence of language varieties within a text shows that dialects, at least on certain parts ofthe territory on which Czech is spoken, still have the potential to be used in texts ofthis kind. The dialectisms, as less formal means of expression, enable the author to react to the reviewed works more spontaneously, to emphasize the attitude of an "ordinary reader" from outside the cultural centre (which is actually the author’s stylization) and to be more spontaneous and emotive than in a typical review; the markedness oflanguage may create a distance from the topic as well. The unusual language also slows the process of perception ofthe text, prevents the reader from cursory reading and thus contributes to a more effective transmission of both facts and emotional attitudes